A new approach to the elucidation of complex chromosome rearrangements illustrated by a case of Rieger syndrome. Issue 3 (March 1998) - Ogilvie, C M; Raymond, F L; Harrison, R H; Scriven, P N; Docherty, Z
Abstract : A patient with a complex chromosome rearrangement and unilateral Rieger syndrome is presented. This rearrangement involves four chromosomes and six breakpoints, one of which is at 4q25, the candidate region for Rieger syndrome. We discuss a novel approach to the elucidation of this case using a multiprobe fluorescence in situ hybridisation method to show rearrangements unpredictable from G banded analysis, and the clear and unambiguous presentation of the karyotype using computer generated colour ideograms.